The Situation of the Elderly in Bangladesh (Bangladesh Journal of Bioethics, 2016)
In Bangladesh due to improved quality of life the number of people over 60 years is increasing rapidly. This should be seen as an emerging challenge as the elderly will have special needs and require different care-giving services. Since Bangladesh does not have a social welfare system there will be competition for inadequate resources specially health and medical services. It is envisaged that due to more elderly population the demographic structure will undergo a slow change from the present pyramid structure.  The growing trend towards nuclear family or where children live abroad will put the elderly parents in a dilemma-the financial and social support that is essential for them has not yet emerged. The nutrition and health status of elderly people depend on adequate food safe water, proper sanitation facilities and maintaining hygienic standards. To provide special medical care for the elderly there is a need to establish WHO recommended Age-Friendly Primary Health Care centers and separate wards /units are to be set up in the hospitals. To reduce vulnerability of older women there is a need to distribute assets and properties according to the law. . Our new generations have to be responsive, informed and attentive about their duties and responsibilities towards the elderly people. Taking proper care of the elderly is our ethical duty and responsibility.